DETERMINATION OF LAMBDA-CYHALOTHRINE IN MICRO-INCAPSULATED INSECTICIDAL COMPOSITIONS - L. A. Nosikova; A. N. Kochetov (Тонкие химические технологии, 2016)
The determination of the title compound in the model microencapsulated insecticidal tools is considered, as well as the ability to conduct analysis in mixtures with other encapsulated means on the basis of a pyrethroid (cypermethrin, deltamethrin, tetramethrin, permethrin, phenothrin, transfluthrin) and phosphorus-containing derived insecticidal substances (chlorpyrifos). The conditions of direct analytical determination and the stage of sample preparation with the previously described methods are adapted. The content of lambda-cyhalothrin together with cypermethrin in microencapsulated compositions is determined by spectrophotometric method taking into account the absorption of trace contaminants - technical substances and building blocks of microcapsules (phospholipids). RP HPLC method shows the possibility of separate determination of lambda-cyhalothrin and several pyrethroids (except for cypermethrin), and chlorpyrifos, in the hypothetical compositions in a joint encapsulating order to obtain a highly active insecticide that enable overcoming the resistance of insects to a number of inactive substances.